Evidence of an XX/XY sex chromosome system in the fish Dormitator maculatus (Teleostei, Eleotrididae) - Oliveira, Claudio [UNESP]; Toledo, Lurdes Foresti de Almeida (Sociedade Brasileira de Genética, 2006)
The fish Dormitator maculatus has a chromosomes number of 2n = 46, females having a karyotype of 14 M, 28 SM, 2 ST and 2A and males 13 M, 28 SM, 3 ST and 2A. The presence of a heteromorphic pair in the males and a corresponding homomorphic pair in the females suggest the occurrence of an XX/XY sex chromosome system in D. maculatus. The putative X chromosome has a pericentromeric C-band positive segment and the putative Y chromosome a C-band positive short arm.
Keywords: fish cytogenetics; karyotypes; Ag-NORs; C-band; sex chromosomes